Digital Economy and Economic Growth in Indonesia: A Panel Data Analysis - Adriani, Evi; Fahmi, Ali; Muslim, Irwan; Eliza, Yulina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Penelitian ini bertujuan untuk menganalisis pengaruh ekonomi This study aims to analyze the impact of the digital economy on economic growth in Indonesia using a panel data approach across provinces. The rapid development of digital technologies, particularly financial technology (fintech) and e-commerce, has driven economic transformation through improved efficiency, expanded market access, and enhanced financial inclusion, although disparities in digital adoption across regions remain a challenge. This research utilizes secondary data analyzed באמצעות panel data regression methods, including the Common Effect Model, Fixed Effect Model, and Random Effect Model, using EViews. The variables employed include digital economy indicators (internet usage, fintech, and e-commerce) along with control variables such as investment and inflation. The results indicate that the digital economy has a positive and significant effect on economic growth. Financial technology improves access to financial services and transaction efficiency, while e-commerce stimulates consumption and business expansion. However, variations across provinces highlight the importance of digital infrastructure readiness and human capital quality. This study emphasizes the need to strengthen digital infrastructure, enhance digital literacy, and implement inclusive policies to support sustainable economic growth in the digital era.